Análise experimental do processo de recuperação de líquidos em meios porosos artificiais por injeção de gás - Xavier, Marcos Versiani Santos (2008)
The liquid displacement in porous media by injection of some kind of fluid isa technique used in several industrial processes like the cleanliness of contaminated soilsand enhanced petroleum recovery in porous media. Such kinds of problems are stronglydependent of the capillarity number characterized by the ratio between viscous forces andsuperficial ones.The present work proposes an experimental investigation of the process ofrecovery of viscous liquids in artificial porous media constituted by glass spheres. It isinvestigated the effect of capillarity number and the mean diameter on fraction of mass,mp, that is left behind. The main results are presented in terms of the effect of capillaritynumber during the breakthrough time. The results are compared with that by Taylor [20]in his study of gas-liquid displacement in capillary tube. This comparison is performedto looking for a relationship between the gas-displacement in capillary tube and the oilrecovery in a more realistic porous media and to prove that the capillary number is, infact, the physical parameter that governs the proposed problem